Revisioning Europe : the films of John Berger and Alain Tanner (2011)
What constitutes political cinema? What debt does it owe simply to poli- tics, or simply to cinema? How can its formal patterns really reflect political concerns? The 1970s were dominated by such debate among film critics and theoreticians, a lot of whom were strongly hostile to narrative, to say noth- ing of pleasure, and a lot of whom were under the spell of Bertolt Brecht. A lot of that is, in retrospect, easily caricatured as quaint, and these sorts of questions have faded from the main stream of Film Studies (at least in English and French). But two people active in these ’70s debates never suc- cumbed to pious, over-simplified equations of narrative identification or visual pleasure with oppression. They were neither film theorists nor film critics, although throughout their work they evince a keenly acute sense of the philosophical and aesthetic stakes of cinema and politics. They worked together only briefly, but the films they made together offered a vision of a political cinema whose rigour and accessibility remains, in many ways, unmatched. “They make one of the most interesting film-making teams in Europe today” Vincent Canby wrote in the New York Times on 2 October 1976.